2020
DOI: 10.32098/mltj.01.2020.02
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Cycle does not Affect the Mechanical Properties of Muscle and Tendon

Abstract: Background. The evidences suggest that the risk of orthopaedic injury is the highest in the ovulation phase of the menstrual cycle. The change on mechanical properties of muscle and/or tendon related the higher estrogen concentration in the ovulation phase may be related to the highest risk of orthopaedic injury in ovulation phase. The purpose of the study was to investigate the menstrual cycle effect on the stiffness, elasticity and/or tone of the medial gastrocnemius muscle, Achilles and patellar tendons. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This may be because, although we measured the stiffness at two different phases, hormonal fluctuations during the menstrual cycle might not be sufficiently effective to induce changes in the properties of muscles at the resting position when muscles are relaxed (less activated). One study suggested that muscles are less affected by the menstrual cycle than tendons, which contain higher collagen levels, considering the effect of oestrogen on collagen level variations (Taş & Aktaş, 2020). The delayed response of hormone fluctuations may be another cause of the obtained result.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because, although we measured the stiffness at two different phases, hormonal fluctuations during the menstrual cycle might not be sufficiently effective to induce changes in the properties of muscles at the resting position when muscles are relaxed (less activated). One study suggested that muscles are less affected by the menstrual cycle than tendons, which contain higher collagen levels, considering the effect of oestrogen on collagen level variations (Taş & Aktaş, 2020). The delayed response of hormone fluctuations may be another cause of the obtained result.…”
Section: Discussionmentioning
confidence: 99%
“…Methods of muscle tone objectification can also contribute to research on the nature of muscle tone and its behavior in specific physiological and pathological circumstances. Some authors have already used USE [ 144 ], MRE [ 145 , 146 , 147 ], or Myoton [ 106 , 109 , 142 , 148 , 149 ] to establish normative values and to investigate changes in muscle rheological properties during the day or as a function of age, gender, menstrual cycle phase, BMI, race, individual physical activity, or stride length. As mentioned above, Myoton has also served to investigate the effect of specific physical activities on the rheological properties of muscle [ 131 , 135 , 136 , 137 ] or how these characteristics further relate to endurance and contractile ability and muscle strength [ 138 , 140 ].…”
Section: Application Of Objective Methods In Muscle Tone Diagnosismentioning
confidence: 99%
“…Muscle mechanical properties of GL were measured at 30% of the distance between fibulae capitulum and Achilles tendon insertion (16), at the central part of muscle belly. AT was measured 2 cm proximal to the superior aspect of the calcaneus (17). The standard flat end probe (3mm diameter) of the Myoton-Pro was placed perpendicular to the surface of the skin at all measurement sites and the device delivers a short mechanical impulse to the skin and below the tissues, directly under the probe (duration: 15 ms; force: 0.3 -0.4 N).…”
Section: Methodsmentioning
confidence: 99%